Detection of Elder Abuse Through Emergency Care Technicians Screening Tool Revision for Home-Based Primary Care (DETECT-RPC): a cluster randomised controlled trial study protocol - Melvin D Livingston; Brad Cannell; Jason Burnett; Nicholas Sevey; Kristin Lees Haggerty; Carolyn Pickering (BMJ Open)
Introduction The annual prevalence of elder mistreatment (EM) in cognitively intact older adults is estimated to be 11%, yet the annual prevalence in older adults with Alzheimer’s disease and related dementias (AD/ADRD) is estimated to be as high as 75%. Associated with a decrease in quality of life and increase in risk of mortality, EM represents a significant public health burden. Home-based primary care (HBPC) providers are uniquely positioned to address the critical need for robust EM screening and reporting, especially among individuals with AD/ADRD. This protocol seeks to adapt the Detection of Elder mistreatment Through Emergency Care Technicians (DETECT) screening tool, previously used by emergency medical technicians, for use by HBPC providers.Methods and analysis The protocol consists of two main phases which include four substudies. Substudy 1 uses a qualitative approach to understand the current barriers to clinician identification and reporting of EM in HBPC, including what adaptations need to be made to DETECT for use in HBPC. Substudy 2 is a cluster randomised controlled trial evaluating the impact of Detection of Elder Abuse Through Emergency Care Technicians Screening Tool Revision for Home-Based Primary Care (DETECT-RPC) on clinician identification of older adult patients with increased risk of EM and referring their concerns to the appropriate authorities and service providers. Substudies 3 and 4 apply a mixed-methods approach to postscreening interviews with clinicians and caregiver/care recipient dyads, respectively. These substudies aim to evaluate DETECT-RPC’s impact on barriers to EM identification and reporting as well as the harms and benefits of using the screening tool from the perspective of patients and their caregivers.Ethics and dissemination All components of this study are conducted with the approval of the Institutional Review Board of the University of Texas Health Science Center at Houston (HSC-SPH-22-0732, HSC-SPH-23-0105, HSC-SPH-23-0965, HSC-SPH-24-0123). The results of this study will be disseminated through a peer-reviewed journal as well as through presentations at professional conferences, invited talks and other standard channels.Trial registration number NCT05958654 (ClinicalTrials.gov).